CHEMICAL COMPOSITION AND ANTIBACTERIAL ACTIVITY OF ESSENTIAL OIL OF MENTHA ARVENSIS L. HARVESTED AT HIGH ALTITUDE ARMENIAN FLORA (Proceedings of the YSU B: Chemical and Biological Sciences, 2023)
Currently it is relevant to reveal possible new sources of natural antibacterial components, the mechanisms of antibiotic resistance formation in bacteria, and the possible ways to overcome the problem of microbial resistance to antibiotics. So, our research aimed to study the chemical composition and antibacterial activity of the essential oil (EO) isolated from the herb Mentha arvensis harvested at high altitude Armenian landscape. Menthol constitutes a significant part of the EO components of the M. arvensis plant, reaching approximately 70%. The investigated EO showed high antimicrobial activity against several Gram-positive and Gram-negative bacterial strains. In particular, the EO equally suppressed the growth of both wild-type and kanamycin-resistant strains of Escherichia coli and manifested the minimal inhibitory concentration against all tested microorganisms of 0.18 mg/mL. So, M. arvensis EO is relevant for application in the food and cosmetic industry as a natural aromatizer and preservative.
Keywords: Mentha arvensis; GC-MS; antibacterial activity; antibiotic resistance